Does habituation really happen? Investigation of psycho-biological responses to body exposure in bulimia nervosa. (March 2017) - Trentowska, Monika; Svaldi, Jennifer; Blechert, Jens; Tuschen-Caffier, Brunna
Abstract: Background: Body exposure is a common and effective treatment for body image disturbance in bulimia nervosa (BN). However, little is known about treatment mechanisms. Based on models of emotional processing and neurovisceral integration, we expected to observe a) initial activation and b) habituation of cognitive-affective and autonomic responding within one and between two standardized body exposure sessions. Methods: A group of 13 women with BN and 13 healthy controls (HC) were repeatedly exposed to their bodies. Prior to and after treatment with three individualized mirror exposure sessions participants received a session of standardized exposure to videographic recordings of their body. Subjective ratings of body-related emotions and thoughts were assessed repeatedly throughout the standardized exposure sessions and autonomic responses were recorded continuously. Results: Subjective and sympathetic responses were activated initially in both groups. Cognitive-affective responses habituated within the standardized sessions in both groups, whereas between the standardized sessions habituation was only found in women with BN. Increasing sympathetic responses were found within the sessions in both groups. Conclusions: The results support cognitive-affective habituation during body exposure in BN and to a lesser extent in HC. Autonomic responses however did not show a corresponding pattern and did not distinguish between groups. Implications for body exposure research and practice are discussed. Highlights: Body image disturbance in Bulimia Nervosa can be treated by body exposure. Underlying mechanisms of body exposure like habituation are unconfirmed. Cognitive-affective and autonomic responses were ascertained during body exposure. Cognitive-affective improvement was found within and between exposure sessions. Initially found autonomic responses did not change further during body exposure.